Coral Covers and The Abundance of Chaetodontidae in Suaka Alam Perairan of Weh Island Aceh - Nadia Aldyza; Ternala Alexander Barus; Miswar Budi Mulya; Muhammad Ali Sarong; Afkar Afkar; Fakhrol Andi; Rahmad Rahmad; Gilang Yuarza (Jurnal Biodjati, 2022)
Pesisir Timur Pulau Weh (PTPW) is a water natural reserve conservation area located in the eastern part of Weh Island. The condition of coral substrates in PTPW has suffered a lot of damage based on bleaching cases that have hit Sabang waters in 2016. Coral conditions can be measured by looking at the abundance of fish indicators of the Chaetodontidae group. Therefore, this study aimed to measure coral conditions and the abundance of Chaetodontidae coral fish, as well as analyze the relationship between the percentage of coral cover and the abundance of Chaetodontidae coral fish. Data of coral were collected using the Point Intercept Transect method with a length of 50 meters, while the abundance of fish used the Underwater Visual Census technique and the Belt Transect method with a length of 50 meters and a total belt width of 5 meters. The results showed that the coral conditions in PTPW were in poor to fair condition with the highest cover at The Sumur Tiga site (36.83%) and the lowest at The Ujung Kareung site (11.5%). The highest abundance of Chaetodontidae fish was found at Ujung Seuke site (1253.3 ind/ha) and the lowest was found at Anoi Itam site (186.7 ind/ha). The results of the correlation analysis between the percentage of coral cover and the abundance of Chaetodontidae coral fish showed a positive relationship (r = 0.482), but it was not significant (p>0.05), and the regression equation obtained Y = 17.16x + 166.52 with a determination coefficient of 18.3%, which indicated that the correlation between the two variables was very weak.